2018
DOI: 10.1111/ijfs.13737
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of buckwheat starch films containing zinc oxide nanoparticles against Listeria monocytogenes on mushrooms

Abstract: Summary Buckwheat starch (BS) films containing zinc oxide nanoparticles (ZnO‐N; 0%, 1.5%, 3% and 4.5%) were prepared, and their physical, optical and antimicrobial properties were examined. As ZnO‐N content increased from 0% to 4.5%, TS increased from 14.99 to 19.09 MPa and E decreased from 25.60% to 20.65%. In addition, L* and a* values decreased, whereas b*, ΔE and opacity increased. Regarding antimicrobial activity, the BS/ZnO‐N films had the reductions of 2.96–3.74 log CFU mL−1 against Listeria monocytogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 41 publications
4
19
0
Order By: Relevance
“…The results of this study confirm the earlier reports of Čabarkapa et al (), who found that buckwheat hull extract could be used for food preservation. Kim and Song () showed that buckwheat starch films containing 3% zinc oxide nanoparticles could be used as a food packaging material. These authors found that buckwheat films exhibited antimicrobial activity against Listeria monocytogenes and maintained the quality of fresh cut mushrooms during storage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study confirm the earlier reports of Čabarkapa et al (), who found that buckwheat hull extract could be used for food preservation. Kim and Song () showed that buckwheat starch films containing 3% zinc oxide nanoparticles could be used as a food packaging material. These authors found that buckwheat films exhibited antimicrobial activity against Listeria monocytogenes and maintained the quality of fresh cut mushrooms during storage.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study confirm the earlier reports of Čabarkapa et al (2008), who found that buckwheat hull extract could be used for food preservation. Kim and Song (2018) showed that buckwheat starch films containing 3% zinc oxide nanoparticles could be used as a food packaging material.…”
Section: Appearancementioning
confidence: 99%
“…Active packaging film with Ag-Cu nanoparticles and 50% CEO showed maximum antibacterial action over 21 days when the samples were stored in the refrigerator [ 77 ]. Buckwheat starch (BS) films containing ZnO nanoparticles showed very good antimicrobial activity, when the concentration of ZnO nanoparticles was 3%, since the obtained film for fresh-cut mushroom packaging demonstrated antimicrobial activity against L. monocytogenes , since the reduction of 0.86 log CFU/g after 6 days of storage was detected [ 78 ]. Maximum CFU reductions of 96% and 64.1% on E. coli growth were obtained using 50/50 ratio of TiO 2 /ZnO nanoparticles-coated low-density polyethylene (LDPE) films at the presence of UV light for film alone and fresh calf minced meat packed, respectively [ 79 ].…”
Section: Food Packagingmentioning
confidence: 99%
“…The conversion of phenol to quinone induced substantial aggregation in the film matrix through non-disulfide bonds, thus controlling the roughness of the film [28]. SEM images of SPI/MPE/ZnO films showed that the higher the concentration of ZnO NPs, the smoother the cross-section structure of the film, and the more uniform the distribution of ZnO NPs in the film matrix [46]. The EDX analysis confirmed the presence of ZnO NPs in the composite films (Figure S4).…”
Section: Sem and Afmmentioning
confidence: 99%